The Effectiveness of Learning Cycle 5E Model toward Students’ Science Process Skills in Natural Science Subject - Sari, Lia; Shalihah, Siti; Pastiyanti, Yeni (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
The Objective to be achieved is to determine the effectiveness of using the Learning Cycle 5E Model in natural science lessons in grade V of MIS Darussalam by looking at the ability of students’ science process skills in the learning and the outcomes. This study used the field research method with a one-group pre–test–post–test model. The population of this study was grade V MIS Darussalam with the sample taken from grade V A which amounted to 15 students. The data collection techniques used were tests, observation, documentation, and interviews. After all the data were collected, then the N-Gain Score test was conducted to see the level of learning effectiveness. The result obtained in this study showed that the Learning Cycle 5E model was effectively used in science subjects with the ability of students’ science process skills reaching 77% in the good category and the student learning outcomes using the Cycle 5E learning model ≥ KKM reached 80% percentage and the result of the N-Gain score obtained a value of 0.6131 which indicates that the effectiveness level of using Learning Cycle 5E model is in the Moderate category.